Erdös-Wintnersche Satz für die geordneten Halbgruppen mit regulärer Normierung - Juškys, Z. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:З. Юшкис. Теорема П. Эрдёша и А. Винтнера на упорядоченных полугруппах с регулярной нормировкойZ. Juškys. P. Erdiošo ir A. Vintnerio teorema sutvarkytuose pogrupiuose su reguliariu normavimu